Effects of Soil Microbes on Functional Traits of Loblolly Pine (Pinus taeda) Seedling Families From Contrasting Climates - Ulrich, Danielle E. M.; Sevanto, Sanna; Peterson, Samantha; Ryan, Max; Dunbar, John (Frontiers in Plant Science, 2020)
Examining factors that influence seedling establishment is essential for predicting the impacts of climate change on tree species’ distributions. Seedlings originating from contrasting climates differentially express functional traits related to water and nutrient uptake and drought resistance that reflect their climate of origin and influence their responses to drought. Soil microbes may improve seedling establishment because they can enhance water and nutrient uptake and drought resistance. However, the relative influence of soil microbes on the expression of these functional traits between seedling families or populations from contrasting climates is unknown. To determine if soil microbes may differentially alter functional traits to enhance water and nutrient uptake and drought resistance between dry and wet populations, seeds of loblolly pine families from the driest and wettest ends of its geographic range (dry, wet) were planted in sterilized sand (controls) or in sterilized sand inoculated with a soil microbial community (inoculated). Functional traits related to seedling establishment (germination), water and nutrient uptake and C allocation (root:shoot biomass ratio, root exudate concentration, leaf C:N, leaf N isotope composition (15N)), and drought resistance (turgor loss point, leaf carbon isotope composition (13C)) were measured. Then, plants were exposed to a drought treatment and possible shifts in photosynthetic performance were monitored using chlorophyll fluorescence. Inoculated plants exhibited significantly greater germination than controls regardless of family. The inoculation treatment significantly increased root:shoot biomass ratio in the wet family but not in the dry family, suggesting soil microbes alter functional traits that improve water and nutrient uptake more so in a family originating from a wetter climate than in a family originating from a drier climate. Microbial effects on photosynthetic performance during drought also differed between families, as photosynthetic performance of the dry inoculated group declined fastest. Regardless of treatment, the dry family exhibited a greater root:shoot biomass ratio, root exudate concentration, and leaf 15N than the wet family. This indicates that the dry family allocated more resources belowground than the wet and the two family may have used different sources of plant available N, which may be related to their contrasting climates of origin and influence their drought...